Problems faced by micro finance institutions in Nigeria: A recent survey - Zuru, Nasiru Liman; Hashim, Mohd Khairuddin; Arshad, Darwina (Elite Hall Publishing House, 2017)
In Nigeria, microfinance institutions (MFIs) have gained acceptance not only as important financial institutions but they are also being recognized for their economic and social contributions in the country.However, as financial institutions, MFIs are not invulnerable to problems.Like the other organizations, MFIs confront difficulties that affect their operations as well as performance. The literature reveals that there is not only limited research but also little information on the problems encountered by MFIs.This study attempts to investigate the problems faced by MFIs in Nigeria.By using questionnaire, the data was collected from 121 MFIs.Based on the analysis of the data gathered from the MFIs, the study detected a number of significant problems faced by these institutions.